Hyperthermia based individual in situ recombinant vaccine enhances lymph nodes drainage for de novo antitumor immunity - Cuixia Zheng; Xinxin Liu; Yueyue Kong; Lei Zhang; Qingling Song; Hongjuan Zhao; Lu Han; Jiannan Jiao; Qianhua Feng; Lei Wang (Elsevier, 2022)
The continuing challenges that limit effectiveness of tumor therapeutic vaccines were high heterogeneity of tumor immunogenicity, low bioactivity of antigens, as well as insufficient lymph nodes (LNs) drainage of antigens and adjuvants. Transportation of in situ neoantigens and adjuvants to LNs may be an effective approach to solve the abovementioned problems. Therefore, an FA-TSL/AuNCs/SV nanoplatform was constructed by integrating simvastatin (SV) adjuvant loaded Au nanocages (AuNCs) as cores (AuNCs/SV) and folic acid modified thermal-sensitive liposomes (FA-TSL) as shells to enhance de novo antitumor immunity. After accumulation in tumor guided by FA, AuNCs mediated photothermal therapy (PTT) induced the release of tumor-derived protein antigens (TDPAs) and the shedding of FA-TSL. Exposed AuNCs/SV soon captured TDPAs to form in situ recombinant vaccine (AuNCs/SV/TDPAs). Subsequently, AuNCs/SV/TDPAs could efficiently transport to draining LNs owing to the hyperthermia induced vasodilation effect and small particle size, achieving co-delivery of antigens and adjuvant for initiation of specific T cell response. In melanoma bearing mice, FA-TSL/AuNCs/SV and laser irradiation effectively ablated primary tumor, against metastatic tumors and induced immunological memory. This approach served a hyperthermia enhanced platform drainage to enable robust personalized cancer vaccination.